(3efXheI WHjIs - (3GdjGaYj , Yaja GdOjf YHO Gddg Hf CSYO Hf Ydj GdjGaYj Gdjefj, Yaja GdOjf,J (B768 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdMGaX GdYGQa GdeMbb fRjd GdMQejf GdTQjajf YHO Gddg Hf CSgO GdjGaYi (B_(3faY Gddg Hg (B- (3gPg GdfHPI fXekG Ydi ebJVi GTgQ s
(3BNQgG (B:s
(3gh BH , hCjdhd , hgPG JeGegG aKb HGdPi Cedi hdGJJhge s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B72 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B34s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B185 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdHdOjI HGdEScfOQjI (B(2139 (3O(B) s
Keywords: (3GdWHs